INCREASING THE ABILITY TO DESCRIBE HEAT AND SOUND ENERGY IN THE ENVIRONMENT USING EXPERIMENTAL METHOD IN CLASS IV STUDENTS OF SDN 1 SOMBRON - Eko Handi Winarko; Fitri Puji Astutik (PROGRES PENDIDIKAN, 2022)
The aims of this study were (1) to determine the improvement of experimentation skills in studying heat and sound energy with the experimental method of fourth grade students at SDN Bagsongan, Kayenkidul District, Kediri Regency, (2) to determine the improvement of the ability to describe heat and sound energy with experimental methods in class students. IV SDN Bangsongan 1, Kayenkidul District, Kediri Regency. This study uses a Classroom Action Research (CAR) approach with the research subjects being fourth graders at SDN Bangsongan 1. The study was conducted in two cycles. Data was collected by using teacher activity observations, student activity observations, performance observations and tests. The data analysis technique used is the average percentage analysis. The results of this study can be concluded that: (1) learning with the experimental method can improve experimenting skills when studying heat and sound energy of fourth grade students of SDN Bangsongan I in the first cycle the student performance results obtained an average of 58.5% and in the second cycle increased to 88%. This is supported by an increase in teacher activity with an average of 66.1% increasing to 89.6% and an increase in student attitudes from 58.3% to 88.7%; and (2) learning with the experimental method can improve the ability to describe heat and sound energy based on the assessment of student test results which is indicated by an increase in the average score of students is 68.61 with a learning mastery percentage of 51.6% in the first cycle and in the second cycle the average the average becomes 79.55 with the percentage of learning completeness 87.1%.